Safety of benzophenone to be used as flavouring. (14th November 2017) - ; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: Benzophenone [FL‐no: 07.032] has been evaluated as a flavouring substance, in FGE.69, by the EFSA Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food in 2008. Benzophenone was evaluated also by JECFA (2011 ) and by IARC (2013 ) based on studies that were not considered in the EFSA opinion on FGE.69. Therefore, the Commission requested the CEF Panel to carry out a review of existing literature on the safety of this flavouring substance. In the framework of the evaluation of benzophenone as a food contact material, the CEF Panel established a tolerable daily intake (TDI) of 0.03 mg/kg body weight (bw) per day (2009). In the present Opinion, the Panel considered the already existing evaluations by EFSA, JECFA, IARC and available literature data on benzophenone toxicity. Moreover, new data on the use levels of benzophenone as a flavouring substance have been provided. The Panel considers that there is no concern with respect to genotoxicity. The Panel considers the endocrine activities of benzophenone and its metabolite 4‐hydroxybenzophenone as weak and not directly related to the observed toxic effects including the neoplastic effects in rodents. The Panel confirms that the conservative approach taken by EFSA (2009 ) to derive a TDI of 0.03 mg/kg bw for benzophenone is appropriate to cover the non‐neoplastic effects in the chronic toxicity studies and the neoplastic effects induced in the rodent carcinogenicity studies. The TDI is in the same order of magnitude as the chronic dietary exposure of adults and children to benzophenone (10–20 μg/kg bw per day) for the amount of added flavouring substance. The Panel considers that the calculated TDI and exposure estimate are based on conservative assumptions. The Panel concludes that there is no safety concern for benzophenone under the current condition of use as a flavouring substance.